2020
DOI: 10.17656/jzs.10804
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic and Blood Group Findings in Children with Acute Leukemia: a single cancer center experience

Abstract: Leukemia is a cancer of white blood cells, in which the bone marrow produces irregular white blood cells. These cells swarm out the solid blood cells. In intense leukemia, the cells are highly irregular, and their number increments quickly. Acute lymphocytic leukemia (ALL) most common childhood malignancy in most parts of the world. The etiology of childhood leukemia is unknown and is probably multifactorial. Leukemia can often be cured. However, the association between this type of cancer and ABO blood group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…The relationship between ALL and ABO blood groups is controversial. [23][24][25][26] suggested that the blood group frequency might be similar among ALL Patients and healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between ALL and ABO blood groups is controversial. [23][24][25][26] suggested that the blood group frequency might be similar among ALL Patients and healthy individuals.…”
Section: Introductionmentioning
confidence: 99%